COVID-19 Pandemic Awareness, Attitudes, and Practices Among the Pakistani General Public - Rehman, Rehana; Jawed, Shireen; Ali, Rabiya; Noreen, Khola; Baig, Mukhtiar; Baig, Javaria (Frontiers in Public Health, 2021)
Abstract Background: Outbreak of COVID-19, in many countries, have imposed a lockdown on their residents. The usefulness of these extenuative actions is extremely reliant on knowledge, attitudes, and practices of society hold toward the pandemic control. Objective: The purpose of this study was to explore the awareness, attitudes and practices of the general Pakistani population about COVID-19. Methods: From 13 June until 30 June 2020, a cross-sectional online KAP survey was conducted among the Pakistani public. For data collection, a validated self - administered questionnaire was used. The survey instrument consisted of 6 demographic characteristics, 14 items on knowledge,4 on attitudes, and 6 items on practices, modified from a previously published questionnaire on COVID-19. Results: A total of 2307 participants, 58.3% males, and 41.7% of females were included in the study after removing the incomplete responses. The majority of 86.7% seek information from social media and television,95% had a good practice, 89.9% had a positive attitude, and two-thirds of 67.4% had adequate knowledge. The students and people from younger age groups had a more positive attitude compared to others. Highly educated individuals demonstrated good practice in contrast with other groups (p<.001). In logistic regression analysis, the odds ratio indicated that the private job was negatively, and high monthly income was positively associated with adequate knowledge (OR=.595). Old age was the predictor of negative attitude and high school degrees, and master's degrees were associated with good practice scores. Conclusion Pakistani general population has an overall positive attitude and proactive practices against COVID -19, but their knowledge is inadequate. The most important source of information was social media and television playing a crucial role in educating the Pakistani public.